2007
DOI: 10.1677/jme-07-0038
|View full text |Cite
|
Sign up to set email alerts
|

Distinct expression and activity profiles of largemouth bass (Micropterus salmoides) estrogen receptors in response to estradiol and nonylphenol

Abstract: The estrogen receptor (ER) signaling cascade is a vulnerable target of exposure to environmental xenoestrogens, like nonylphenol (NP), which are causally associated with impaired health status. However, the impact of xenoestrogens on the individual receptor isotypes (a, ba, and bb) is not well understood. The goal of these studies was to determine the impact of NP on largemouth bass (Micropterus salmoides) ER isotype expression and activity. Here, we show that hepatic expression levels of three receptors are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 68 publications
5
38
0
Order By: Relevance
“…30) On the other hand, Sabo-Attwood et al reported that transcription of the ERα subtype is predominantly induced in concert with VTG in largemouth bass exposed to E2, and that ERβ subtypes depress ERα activation. 32) Moreover, Leaños-Castañeda and Van Der Kraak measured VTG induction in cultured liver cells from rainbow trout cells treated with ERα-or ERβ-selective ligands, and VTG induction was observed in ERβ-selective ligand-treated cells, but was not induced with the ERα-selective ligand. 31) To our knowledge, however, no information is currently available on the participation and functional distinction of ERα and ERβ in VTG1 and VTG2 synthesis after treatment with estrogenic compounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30) On the other hand, Sabo-Attwood et al reported that transcription of the ERα subtype is predominantly induced in concert with VTG in largemouth bass exposed to E2, and that ERβ subtypes depress ERα activation. 32) Moreover, Leaños-Castañeda and Van Der Kraak measured VTG induction in cultured liver cells from rainbow trout cells treated with ERα-or ERβ-selective ligands, and VTG induction was observed in ERβ-selective ligand-treated cells, but was not induced with the ERα-selective ligand. 31) To our knowledge, however, no information is currently available on the participation and functional distinction of ERα and ERβ in VTG1 and VTG2 synthesis after treatment with estrogenic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] Therefore, functional analysis and the effects of estrogenic chemicals need to be assessed for each ER subtype in fish; however there are currently few such studies. [30][31][32] 33) On the other hand, novel E2 analogs were synthesized by Kato,34) however, they have never been tested for the affinity against ERα and β.…”
Section: Introductionmentioning
confidence: 99%
“…Vitellogenin (Vtg) is a major egg yolk precursor protein that can be used as a biomarker to indicate an organism's exposure to ED [61]. The gene for this protein is expressed in the liver of oviparous animals under the control of estrogen [57,[62][63][64]. Male fish, under natural conditions, should have very low doses of Vtg since they do not produce eggs.…”
Section: +mentioning
confidence: 99%
“…However, if male fish are exposed to estrogen or to estrogen mimics in the environment, the Vtg gene is turned on. The dynamic range of this protein in normal male fish is 10-50 ng/ml in plasma and ~20 mg/ml in females producing eggs [64]. There have been reports of finding as much as 100 mg/ml in some fish that were induced with estrogen [65].…”
Section: +mentioning
confidence: 99%
“…Although Vtg from one species is limited in its application as a probe for another, some segments of Vtg are highly conserved among species, suggesting the possibility of developing antibodies with wide cross-reactivity [17]. Enzyme-linked-immunosorbent-assay [12,[15][16][17][18], quartz crystal microbalance [13] and yeast cell-based assay [14] are typically used as Vtg detection methods, however, these methods are not suitable for on-field, real-time measurements. Recently, AlGaN/GaN high electron mobility transistors (HEMT) have shown potential as low cost, fast, and accurate sensors in a variety of chemical and biological applications [20][21][22][23][24][25][26].…”
mentioning
confidence: 99%